Peripheral Biomarker for Vascular Disorders. Issue 13 (November 2018) - Shad, Kaneez Fatima; Luqman, Nazar; Simpson, Ann M; Lal, Sara
Atherosclerosis is the underlying cause of most myocardial infarction (MI) and ischaemic stroke episodes. An early sign of atherosclerosis is hypertrophy of the arterial wall. It is known that increased intima media thickness (IMT) is a non-invasive marker of arterial wall alteration, which can easily be assessed in the carotid arteries by high-resolution B-mode ultrasound. Similarly, the other key element of MI and ischaemic strokes is the N-methyl-D-aspartate (NMDA) receptor which is an ionotropic glutamate receptor that mediates the vast majority of excitatory neurotransmission in the brain. NMDA activation requires the binding of both glutamate and a coagonist like D-serine to its glycine site. A special enzyme, serine racemase (SR), is required for the conversion of L-serine into D-serine, and alterations in SR activities lead to a variety of physiological and pathological conditions ranging from synaptic plasticity to ischemia, MI, and stroke. The amount of D-serine available for the activation of glutamatergic signalling is largely determined by SR and we have developed ways to estimate its levels in human blood samples and correlate it with the IMT. This research based short communication describes our pilot study, which clearly suggests that there is a direct relationship between the SR, D-serine, and IMT. In this article, we will discuss whether the activity of SR can determine the future consequences resulting from vascular pathologies such as MI and stroke.